Targeting the IKZF1/BCL-2 axis as a novel therapeutic strategy for treating acute T-cell lymphoblastic leukemia - Juan Li; Chunmei Ye; Hui Li; Jun Li (Cancer Biology & Therapy)
Objectives Acute T-cell lymphoblastic leukemia (T-ALL) is a severe hematologic malignancy with limited treatment options and poor long-term survival. This study explores the role of IKZF1 in regulating BCL-2 expression in T-ALL.Methods CUT&Tag and CUT&Run assays were employed to assess IKZF1 binding to the BCL-2 promoter. IKZF1 overexpression and knockdown experiments were performed in T-ALL cell lines. The effects of CX-4945 and venetoclax, alone and in combination, were evaluated in vitro and in vivo T-ALL models.Results CUT&Tag sequencing identified IKZF1 binding to the BCL-2 promoter, establishing it as a transcriptional repressor. Functional assays demonstrated that IKZF1 overexpression reduced BCL-2 mRNA levels and increased repressive histone marks at the BCL-2 promoter, while IKZF1 knockdown led to elevated BCL-2 expression. CX-4945, a CK2 inhibitor, could reduced BCL-2 levels in T-ALL cells. Notably, knockdown of IKZF1 partially rescued the CX-4945-induced repression of BCL-2. These results underscore the CK2-IKZF1 signaling axis as a key regulator of BCL-2 expression. In vitro, CX-4945 enhanced the cytotoxicity of venetoclax, with the combination showing significant synergistic effects and increased apoptosis in T-ALL cell lines. In vivo studies with cell line-derived xenograft (CDX) and patient-derived xenograft (PDX) models demonstrated that CX-4945 and venetoclax combined therapy provided superior therapeutic efficacy, reducing tumor burden and prolonging survival compared to single-agent treatments.Conclusions IKZF1 represses BCL-2 in T-ALL, and targeting the CK2-IKZF1 axis with CX-4945 and venetoclax offers a promising therapeutic strategy, showing enhanced efficacy and potential as a novel treatment approach for T-ALL.